Analisis Tingkat Bagi Hasil Mudharabah: di Tinjau dari Rasio Return on Assets (ROA), Financial to Deposit Ratio (FDR) dan Biaya Operasional dari Pendapatan Operasional (BOPO) (Studi pada Bank Umum Syariah di Indonesia Periode 2014-2018) - Bayu Tri Cahya; Rikha Zakiyah; Rukmini Rukmini; Aryanti Muhtar Kusuma (Jurnal Ilmiah Ekonomi Islam, 2020)
This study aims to determine the influence of return on assets (ROA), financing to deposit ratio (FDR), and Operating Cost from Operating Income of profit sharing rate for mudharabah deposits. The population in this study is 14 islamic banks in Indonesia and the total sample used is 7 islamic banks. Determination of the sample using nonprobability sampling with technique using purposive sampling with criteria for Islamic banks that issue quarterly financial reports in full in the year 2014-2018. The method of data analysis using multiple regression analysis with SPSS version 23. The results of this study indicate that the variable ROA and BOPO partially have a positive and significant influence on profit sharing rate for mudharabah deposits. While the variable FDR have a negative on profit sharing rate for mudharabah deposits.